Association of Baldness with Coronary Artery Disease and Its Severity: - Arefi, Reza; Pishgahi, Mehdi; Joharimoghaddam, Adel; Momeni, Mohammad Ali; Khoshfetrat, Mehran (Galen Medical Journal, 2020)
Background: The pivotal role of baldness as a potential risk factor for cardiovascular disorders remains a debate, and the small body of literature has generated inconsistent findings. We aimed to assess the association between baldness and the risk for coronary artery disease (CAD) and its severity in a sample of Iranian men. Materials and Methods: This cross-sectional study was performed on 105 consecutive patients suspected to CAD and scheduled for elective coronary angiography. The severity of CAD was determined according to the number of involved coronary vessels. For assessing the severity of baldness, the Hamilton-Norwood scale for grading of androgenetic alopecia in males was used. Results: The overall frequency of CAD in the groups with and without baldness was 88.9% and 72.5%, respectively, indicating a significant difference (P=0.033). Similarly, patients with the family history of baldness suffered more from CAD as compared to those without history (93.3% vs.76.0%). However, no significant association was found between the baldness and non-baldness groups with regard to the severity of CAD (P=0.291). According to the multivariable logistic regression model, the presence of baldness could predict the increased likelihood of CAD (or=3.037, P=0.046). Conclusion: Along with traditional risk factors for CAD, the presence of baldness and positive family history of this phenotype could be considered as the primary determinant for the increasing likelihood of CAD. [GMJ.2020;9:e1474]